Development of Islamic Religious Education Curriculum Design Based on Learning Outcomes in the Implementation of the Independent Curriculum - Rahayu Suprapti; Meli Puspita; Abdurrahmansyah; Nurlaila (Sustainable, 2026)
The implementation of the Independent Curriculum in Indonesia has introduced significant changes in educational practices, particularly in promoting competency-based and student-centered learning. Within this framework, learning outcomes serve as a fundamental component in guiding curriculum design, instructional strategies, and assessment processes. This study aims to develop a conceptual framework for Islamic Religious Education curriculum design based on learning outcomes in the implementation of the Independent Curriculum. The research employs a qualitative approach using library research methods by analyzing relevant academic literature, policy documents, and previous studies related to curriculum development, learning outcomes, and Islamic Religious Education. Data were collected through a systematic literature review and analyzed using qualitative analysis techniques involving data reduction, data display, and conclusion drawing. The findings indicate that a learning outcomes-based curriculum design for Islamic Religious Education should be developed through several systematic stages, including needs analysis, formulation of learning objectives, selection and organization of learning materials, design of learning experiences, and development of appropriate assessment strategies. This approach ensures alignment between curriculum objectives, teaching activities, and evaluation methods while promoting the development of students’ cognitive, affective, and psychomotor competencies. Furthermore, the integration of innovative teaching strategies and digital learning resources can enhance the effectiveness of curriculum implementation. The study concludes that a learning outcomes-based curriculum design supports the goals of the Independent Curriculum by fostering meaningful learning experiences and strengthening students’ moral character, critical thinking skills, and social responsibility.